Cultural categorization of febrile illnesses in correlation with herbal remedies used for treatment in Southwestern Nigeria (2003)
The ethnographic study was conducted in two communities in Oyo state in Southwestern Nigeria. The study sites consisted of a rural and an urban local government area located in the tropical rain forest zone of Nigeria. The study was designed to obtain information on febrile illnesses and herbal remedies for treatment with the aim of identifying potential antimalarial drugs. The study revealed that fever is a general term for describing illnesses associated with elevated body temperature. The indigenous Yoruba ethnic population has categorized fever based on symptoms and causes. The present communication is the result of focus group discussion and semi-structured questionnaire administered to traditional healers, herb sellers, elders and mothers. This was on types of fevers, symptoms and causes of febrile illnesses. The investigation also included use of traditional herbs in the prevention and treatment of the illnesses in the two communities. A total 514 respondents were interviewed. This was made up of 266 (51.8%) from Atiba local government area (LGA), an urban centre while 248 (48.2%) respondents were interviewed from Itesiwaju LGA, a rural community. The LGAs are located in Oyo State of Nigeria. The respondents proffered 12 types of febrile illnesses in a multiple response answering system in Yoruba language. The most common ones (direct translation into English) were: yellow fever (39.1%), typhoid (34.8%), ordinary (28.8%), rainy season (20.8%) and headache (10.5%) fevers respectively. Perceived causes each of the febrile illnesses included stress, mosquito bites, unclean water, rains and over exposure to the sun. Methods of fever prevention were mainly with the use of herbal decoctions, powdered herbs, orthodox medications and maintenance of proper hygiene. Of a total or 112 different herbal remedies used in the treatment or the febrile illnesses compiled from the study, 25 recipes are presented. Recipes consisted of 2-7 ingredients. Oral decoctions (84%), oral powders (63%). use as soaps and creams (40%) in a multiple response system, were the most prevalent routes of administration of prepared herbs used in the treatment of the fevers. Boiling in water or alcohol was the most common method used in the preparation of the remedies. The four most frequently mentioned (multiple response system) plants in the Southwest ethnobotany for fevers were Azadirachta indica (87.5%). Mangifera indica (75.0%), Morinda lucida (68.8%) and Citrus medica (68.8%).